Beta therapy with 90 strontium as single modality therapy for canine squamous cell carcinoma in third eyelid - Andrade, Alexandre Lima de [UNESP]; Fernandes, Marco Antônio Rodrigues [UNESP]; Sakamoto, Silmara Sanae [UNESP]; Luvizotto, Maria Cecília Rui [UNESP] (Universidade Federal de Santa Maria, 2015)
The purpose was to evaluate the effectiveness of beta-radiation with strontium-90 as single modality treatment of canine third eyelid squamous cell carcinoma (SCC). Nine dogs diagnosed with third eyelid SCC were treated with strontium-90. Radiation therapy was administered in four fractions of 100cGy per site every four days and at a depth of 0.2cm (Strontium-90 build' up) in each fraction. Radiation with beta therapy was well tolerated in all animals with no occurrence of radiation induced cataracts. In all cases, there were increased signs of conjunctival inflammation around the mass, which subsided with topical anti-inflammatory. Two dogs required surgical treatment for local tumor recurrence at 150 days and 352 days. In the remaining seven cases, disease free interval ranged from 1239 days to 2555 days. Beta therapy using 90Sr may be a valid alternative for the treatment of third eyelid SCC in dogs

O objetivo foi avaliar a eficácia da betaterapia com estrôncio-90 como modalidade única de tratamento em carcinomas de células escamosas (CEC) da terceira pálpebra de cães. Nove cães foram diagnosticados com CEC de terceira pálpebra, que foram tratados com estrôncio-90. A radioterapia foi administrada em quatro frações de 100cGy por local, a cada quatro dias e a uma profundidade de 0,2cm em cada fração. A betaterapia foi bem tolerada por todos os animais, sem ocorrência de catarata induzida pela radiação. Em todos os casos, houve um aumento dos sinais de inflamação da conjuntiva ao redor da neoformação, as quais cederam com o uso de anti-inflamatório tópico. Em dois cães houve a necessidade de tratamento cirúrgico, pois houve recorrência local do tumor aos 150 dias e aos 352 dias. Nos outros sete casos, o intervalo livre de doença variou entre 1.239 dias e 2.555 dias. Betaterapia usando 90Sr pode ser uma alternativa válida para o tratamento do CEC da terceira pálpebra em cães
Betaterapia com estrôncio-90 como modalidade única de terapia para o carcinoma de células escamosas na terceira pálpebra em cães
Keywords: Beta-radiation; Radiotherapy; Ocular tumor; Adnexa ocular; Dogs; Radiação beta; Radioterapia; Tumor ocular; Anexo ocular; Cães